Human-Centred Branding in the Emerging Context of Narratives Warfare: Based on Worth-Living Marketing Management - Esmaeili, Zohreh Ali; Sobhanifard, Yaser (Journal of Ecohumanism, 2025)
The recent global events involving the Ukraine-Russia war and the Gaza-Israel have highlighted the increasing complexity of brand interactions with the brand community in the context of narrative warfare. Furthermore, various industries are embracing the concept of Industrial Revolution 5.0, emphasising human-centeredness that is value-driven. Based on this, this research aims to explore the dimensions of human-centred branding based on worth-living marketing management in the context of narrative warfare. Design/methodology: This research methodology is a systematic literature review encompassing an in-depth examination of 52 scientific articles and books, complemented by 23 articles from specialised marketing sites and 16 news articles specifically focused on the two most recent wars. Findings: Findings show that the context of the war of narratives encompasses 10 key dimensions and human-centred branding based on worth-living marketing management in narrative warfare contexts, which includes 14 main concepts. Practical implications: The findings of this research give valuable insight to brands (personal, corporate, government, political) to reduce the amount of their calculation errors in the unstable conditions of narrative warfare and to manage existing risks with more precise strategic management. Social implications: This research strengthens the brand’s responsibility towards human issues, such as social, environmental, ethical, and political issues, and accordingly adds to the meaning of collective life, ethics, and collective trust. Originality/value: This research is a pioneer in the in-depth study of the intersection of narrative warfare and human-centred branding, and exploring the dimensions of these two concepts and combining them adds to the value of the existing literature.